Chopped Basalt Fibers Reinforced Mortar for Strengthening the Architectural Heritage - Micaela Mercuri; Marco Vailati; Amedeo Gregori (Fibers)
The high seismic vulnerability of unreinforced masonry buildings urgently calls for researchers to develop sustainable reinforcing methods and materials. This paper presents an innovative lime-based mortar reinforced with randomly oriented basalt fibers for the reinforcement of masonry heritage. The main aim of this study is to understand the effect of the content and the length of basalt fibers on the mortar’s mechanical behavior. As a cementitious material made mostly out of lime, the mortar is chemically compatible with the historical substrate and therefore suitable in cases of restoration works on architectural heritage. Moreover, the chopped basalt fibers are randomly oriented, and this characteristic makes the overall layer effective in all directions, as the state of stress induced by seismic action is directionally undetermined. The newly proposed reinforcement system is characterized by a twofold aspect related to sustainability: 30% of the aggregates composing the mortar mix design is a recycled result of the ruins of the 2009 L’Aquila earthquake, and the chopped fibers are made out of basalt, widely known for its environmentally supportable peculiarity. The study consists of testing samples characterized by two fiber lengths and six fiber contents, along with one set of plain mortar samples. Specimens measuring 160 mm × 40 mm × 40 mm are first tested in a three-point bending (TPB) configuration, aiming to determine the flexural strength and the post-peak capacity through the calculation of the fracture energy. Then, the two broken pieces resulting from the TPB tests, each measuring 80 mm × 40 mm × 40 mm, are tested in splitting and compression, respectively, aiming to compute the tensile and compressive strengths. Finally, to provide a trend for the mortar’s mechanical properties, a regression analysis is performed by fitting the experimental data with simple linear, polynomial, and exponential regression models. Results show that: (i) both fiber content and fiber length are responsible for a linear increase of the flexural strength and the fracture energy; (ii) for both short- and long-fiber mortar samples, the tensile strength and the compressive strength parabolically increase with the fiber content; (iii) the increase in fiber content and fiber length always generates a reduction in the conglomerate workability. The fiber content (FC) optimization with respect to the mechanical properties leads to a basalt FC equal to 1.2% for long-fiber samples and an FC equal to 1.9% for short-fiber ones.